1984
DOI: 10.1111/j.1399-3011.1984.tb00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic, aza‐glycine analogues of luteinizing hormone‐releasing hormone

Abstract: The effect of combination of the hydrophilic aza-Gly substitution (NHNHCO) at position 1 0 with hydrophobic, unnatural D-amino acids in position 6 o n the potency of luteinizing hormone-releasing hormone (LH-RH) analogues has been investigated. Previously the aza-Gly residue was shown to provide protection from enzymatic cleavage and lead t o potency increases in a less hydrophobic series. The compounds were prepared by coupling of the corresponding nonapeptide acids with semicarbazide hydrochloride by the N,N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Additionally, incorporation of the azaGly 51 residue improved metabolic stability of the Phe 50 -Gly 51 and Gly 51 -Leu 52 bonds, which were resistant to serum proteases such as chymotrypsin, NEP, and MMP-9. Although a variety of aza amino acid analogs of biologically active peptides has been reported with improved biological potency, [37][38][39][40][41][42][43][44][45][46][47][48][49] this study is the first report that aza amino acid replacement is a simple way to protect both fragile amide bonds at the N-terminal and C-terminal of the aza amino acid residue.…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, incorporation of the azaGly 51 residue improved metabolic stability of the Phe 50 -Gly 51 and Gly 51 -Leu 52 bonds, which were resistant to serum proteases such as chymotrypsin, NEP, and MMP-9. Although a variety of aza amino acid analogs of biologically active peptides has been reported with improved biological potency, [37][38][39][40][41][42][43][44][45][46][47][48][49] this study is the first report that aza amino acid replacement is a simple way to protect both fragile amide bonds at the N-terminal and C-terminal of the aza amino acid residue.…”
Section: Introductionmentioning
confidence: 97%
“…Azapeptides possess one or more semicarbazide residues from replacement of a backbone α-carbon by nitrogen in the peptide sequence ( Figure 1) [1][2][3][4][5][6][7][8][9][10][11]. The conformation of the azapeptide is thus rigidified, because of the planarity of the urea and the lone-pair repulsion between adjacent nitrogen in the semicarbazide moiety, such that the φ and ψ dihedral angles of the aza-residue backbone have a tendency to adopt turn geometry, as shown by computational, spectroscopic and X-ray crystallography [1][2][3][4][5][6][7]11].…”
Section: Scope and Commentsmentioning
confidence: 99%
“…Moreover, the semicarbazide residue can bestow the azapeptide with improved pharmacokinetic properties, such as longer duration of action and resistance to proteases relative to natural peptides. [1,[8][9][10][11] Methods for the synthesis of azadipeptides have been reviewed with emphasis on the issues of side product formation, such as hydantoin from intramolecular cyclization of activated carbamato and isocyanato amides, and oxadiazalone on activation of carbazates with phosgene equivalents ( Figure 2) [1,11]. The issue of oxadiazalone formation has been surmounted in the synthesis of the aza-glycinyl dipeptide in solution by employing benzophenone hydrazone as the aza-Gly precursor [12].…”
Section: Scope and Commentsmentioning
confidence: 99%
“…Investigations in peptide mimicry have also shown that certain structural changes, when introduced into a peptide, can prevent enzyme degradation and induce conformational preferences that mimic the biologically active secondary structure4. Among the modifications found in peptide mimicry, aza‐peptides, in which one or more residue is replaced by an aza‐amino acid5, have found promising utility in enhancing the drug‐like character of peptide candidates6, by increasing the duration of action7 and resistance to enzymatic degradation8, 9 (see Figure 1 for relevant examples). Furthermore, aza‐amino acid residues have been shown to stabilize β‐turn conformations in peptides as detected by computational10–12, spectroscopic13–15 and crystallographic analyses13.…”
Section: Introductionmentioning
confidence: 99%